Cyberbullying y sexting - Tapia Helfer, Maria-Jimena (2020)
The present state of the art seeks to describe how the online risk behaviors of cyberbullying and sexting in adolescents, between 11 and 18 years old, are being investigated in the last five years at an international and national level. Current studies explain the relationship between two from different theoretical perspectives. On the one hand, sexting is associated with cyberbullying when information is shared through communication networks without prior consent; while cyberbullying is related to sexting when it is pressured by virtual means to carry out the practice of sexting. Most of the reserach found emphasize the frequency of both behaviors, although very few provide information on the individual and social factors that influence the correlation. Thus, the role of the psychologist should be oriented towards the systematization of each behavior, formulate new theoretical models specifically of behavior in cyber space, validate or create evaluation instruments with solid psychometric properties, and adapt or create prevention programs on both behaviors. Likewise, it must include the active participation of other agents involved in education such as teachers, legislators, psychiatrists and definitely parents to intervene from the educational context in favor of the proper use of information and communication technology (ICT).